Sleep-driven prefrontal cortex coordinates temporal action and multimodal integration - Ahmed Z. Ibrahim; Kareem Abdou; Masanori Nomoto; Kaori Yamada-Nomoto; Reiko Okubo-Suzuki; Kaoru Inokuchi (Molecular Brain, 2025)
Abstract Cognitive processes such as action planning and decision-making require the integration of multiple sensory modalities in response to temporal cues, yet the underlying mechanism is not fully understood. Sleep has a crucial role for memory consolidation and promoting cognitive flexibility. Our aim is to identify the role of sleep in integrating different modalities to enhance cognitive flexibility and temporal task execution while identifying the specific brain regions that mediate this process. We have designed “Auditory-Gated Patience-to-Action” Task in which mice should process different auditory signals before action execution as well as analyzing the visual inputs for feedback of their action. Mice could learn the task rule and apply it only after sleeping period and could keep the performance constant across sessions. c-fos positive cells showed the involvement of prelimbic cortex (PrL) during task execution. Chemo-genetic inhibition verified that PrL is required for proper signal response and action timing. These findings emphasize that sleep and cortical activity are keys for cognitive flexibility in adapting to different modalities.